Investigation on conducted EMI noise source impedance extraction for electro magnetic compatibility based on SP‐GA algorithm. Issue 7 (7th June 2019) - Mengxia, Zhou; Yang, Zhao; Wei, Yan; Yi, Cao; Moeed, Abdul; Yinsen, Jia; Xi, Wang
Abstract : A new approach employing scattering parameters (SPs) and genetic algorithm (GA) (SP‐GA) is proposed for modelling conducted electromagnetic interference (EMI) noise source impedance. Based on the principle of SPs, the source impedance is measured through transmission and reflection parameters from a vector network analyser when the circuit is shorted and loaded with noise source impedance, respectively. Moreover, amplitude‐frequency performance and phase‐frequency performance are optimised by using GA, and therefore the equivalent resistance, capacitance, and inductance are attained following the usual formula of the phase and amplitude of source impedance. This work made contribution for the design of the conducted EMI filter.